2020
DOI: 10.2147/tcrm.s233512
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence, Predictors, and Prognosis of Coronary Slow-Flow and No-Reflow Phenomenon in Patients with Chronic Total Occlusion Who Underwent Percutaneous Coronary Intervention</p>

Abstract: Background: The incidence and prognosis of coronary slow-flow (CSF) and no-reflow phenomenon (NRP) in patients with coronary chronic total occlusion (CTO) who underwent percutaneous coronary intervention (PCI) remain unclear. Methods: This single-center prospective study aimed to investigate the incidence of CSF/ NRP during CTO interventional therapy, determine predictors of CSF/NRP, and evaluate its effect on patient outcomes. Results: In this study, 552 patients with CTO who underwent PCI were included. CSF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
11
1
4
Order By: Relevance
“…It was found that stent diameter > 3 mm was associated with higher likelihood of no reflow. Similar reports have also been reported 15,17 .…”
Section: Discussionsupporting
confidence: 91%
“…It was found that stent diameter > 3 mm was associated with higher likelihood of no reflow. Similar reports have also been reported 15,17 .…”
Section: Discussionsupporting
confidence: 91%
“…It is hypothesized that these factors increase procedural difficulty as well as the length of procedure, which in turn increases the probability of PMI. Another study showed that about 16.1% of patients who underwent CTO-PCI had coronary slow-flow and no-reflow phenomenon, and these patients were also more likely to develop PMI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…población estudiada 19 , así como de los métodos usados para detectar el fenómeno de NR. El mecanismo entre la asociación de la función renal y el fenómeno de NR es desconocido, se ha sugerido una posible asociación entre la disfunción renal con la función alterada en las resistencias periféricas de los vasos sanguíneos, lo que condiciona una enfermedad microvascular originada en un desequilibrio en las vías del óxido nítrico 20 .…”
Section: Discussionunclassified
“…De acuerdo con los resultados principales de nuestro estudio, la ER manifestada con una disminución de la tasa de filtración glomerular, un valor de ER KDIGO ≥ 3 y una disminución de la depuración de creatinina; así como un nivel elevado de glucosa y un valor en la clasificación de TIMI basal ≤ 2, se presentaron como predictores independientes en la incidencia del fenómeno de NR en un grupo de pacientes con IAMCEST que fueron tratados con ICP en el noroeste de México. Estos datos discrepan de estudios similares que han sugerido a la edad avanzada, los niveles de CPK, el sitio del infarto y la hiperlipidemia como los principales predictores de la ocurrencia del fenómeno de NR 6 , 17 , las diferencias observadas pueden deberse a variaciones en la población estudiada 19 , así como de los métodos usados para detectar el fenómeno de NR.…”
Section: Discussionunclassified